Highly sensitive titanium-based MXene-reduced graphene oxide composite for efficient electrochemical detection of cadmium and copper ions in water - Mohanadas, Dharshini; Rohani, Rosiah; Abdul Rahman, Siti Fatimah; Mahmoudi, Ebrahim; Sulaiman, Yusran (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
An electrochemically active and promising binary composite that is made up of titanium-based MXene (Ti3C2Tx) and rGO is developed to simultaneously detect the Cd2+ and Cu2+, in water. XRD, FTIR, Raman, XPS, FESEM, elemental mapping, and EDX analysis affirmed the successful formation of the Ti3C2Tx-rGO composite. The produced Ti3C2Tx-rGO electrode exhibited a homogeneous rGO sheet covering the Ti3C2Tx MXene plates with all the detailed Ti2p, C1s, and O1s XPS peaks. The high-performance Ti3C2Tx-rGO composite was successfully tested for the Cd2+ and Cu2+ ions via differential pulse voltammetry (DPV), altering the pH, concentration, and the real water sample’s quality. The electrochemical performances revealed that the proposed Ti3C2Tx-rGO composite depicted excellent detection and quantification limits (LOD and LOQ) for both Cd2+ (LOD = 0.31 nM, LOQ = 1.02 nM) and Cu2+ (LOD = 0.18 nM, LOQ = 0.62 nM) ions, where the result is highly comparable with the reported literature. The Ti3C2Tx-rGO was proven highly sensitive towards Cd2+ (0.345 μMμA−1) and Cu2+ (0.575 μMμA−1) with great repeatability and reproducibility properties. The Ti3C2Tx-rGO electrode also exhibited excellent stability over four weeks with a retention of 97.86% and 98.01% for Cd2+ and Cu2+, respectively. This simple modification of Ti3C2Tx with rGO can potentially be advantageous in the development of highly sensitive electrochemical sensors for the simultaneous detection of heavy metal ions.